Testing of the Efficacy of Bee Probiotic Lactobacilli Under In Vivo Conditions - Kuzyšinová K.; Mudroňová D.; Toporčák J.; Molnár L. (Folia Veterinaria, 2023)
American foulbrood is amongst the most dangerous diseases of the bee-family affecting many honeybee colonies worldwide. In countries of European Union, based on veterinary legislation, the bee colonies tested positive to American foulbrood are eradicated with high economic losses. It is therefore necessary to look for effective prevention, especially by the using of natural ingredients such as probiotics. In this study, we used lactobacilli isolated from digestive tracts of adult healthy honey bees and selected based on their good probiotic properties and ability to inhibit the growth of Paenibacillus larvae. These isolates were identified as Lactobacillus brevis and Lactobacillus plantarum. Night cultures of both strains were used for the preparation of probiotic suspensions and pollen was selected as an appropriate carrier for application of probiotic lacto-bacilli to the hives. Half a litre of pollen suspension was prepared for each hive. The suspension for experimental hives contained probiotic lactobacilli in concentration of 107–108 CFU.ml−1. Bees in control hives received pollen suspension without addition of probiotic lacto-bacilli. The suspensions were supplied to bees three times, once a week. Before and during administration of probiotics, samples of honey bees from each hive were taken every week and numbers of lactobacilli, P. larvae, enterobacteria and coliform bacteria were determined in their digestive tracts. Four weeks after the first administration of probiotic-pollen solution the numbers of lactobacilli were increased approximately by 0.5 log. Before starting this experiment, P. larvae (approx. 107 CFU.ml−1) were detected in digestive tracts of honey bees. In the experimental group after 3 weeks and in the control group after 4 weeks, no viable counts of P. larvae were found. The numbers of enterobacteria, coliform bacteria and Bacillus sp. decreased in both groups. During the experiment the health and condition of the hives were monitored. In addition, also monitored were: the development of the bee colony, the number of dead bees, the amount of hive debris, the aggressiveness of the bees, and the amount of honey spun; later during the autumn treatment also the fall of Varroa jacobsoni was noted. In the experimental and control groups, we recorded a decrease in the amount of hive debris. Only in the experimental group was a slightly above-average development of the bee colony, slightly above-average honey yields and a 70 % lower drop of Varroa mites. Based on these results, we assumed that the probiotic-pollen solution had a positive influence on the composition of microbiota in bee digestive tracts and it can increase resistance to P. larvae. It also had a positive effect on the health and condition of the bee colony. Probiotic-free pollen solution showed similar but weaker effects.